Kemudahan Pembayaran di Era Digital: Telaah Fikih Kontemporer terhadap Praktik Keuangan Modern - A'imatul Kutbaniyah (Lembaga Yasin AlSys, 2025)
The rapid development of digital financial services such as online lending (pinjol) and PayLater has created new challenges for Muslim communities, as their mechanisms frequently involve interest, ambiguous contractual terms, and late payment penalties that potentially conflict with the principles of Islamic law. This study aims to analyze the conformity of pinjol and PayLater systems with contemporary fiqh by identifying elements of riba, gharar, and tadlis in their operational practices. A qualitative, library-based research design is employed by examining classical fiqh literature, fatwas issued by DSN-MUI, regulations of OJK and BI, as well as recent academic studies on fintech and Islamic economic law. The findings show that the majority of conventional pinjol and PayLater services impose pre-agreed additional charges, percentage-based penalties, and unclear contractual information, thereby failing to meet the principles of justice and transparency in muamalah. The study concludes that such digital financial practices cannot be deemed sharia-compliant unless the contractual structures are reformulated and all interest-based charges and riba-based penalties are removed. The implications underscore the urgency of developing sharia-compliant digital financial alternatives, such as murabahah, qardh hasan, ijarah, and profit-sharing fintech models, to provide Muslim communities with safe and lawful financial access, as well as the importance of enhancing Islamic financial literacy to prevent consumptive behavior and recurrent debt traps.